Osmotic Dehydration of Pineapple with Sucrose: Mass Transfer Kinetics - Dhingra, Devinder; Kadam, Dattatreya M.; Singh, Jasjit; Patil, R. T. (Journal of Agricultural Engineering, 2014)
Osmotic dehydration of pineapple (Ananas comosus Linn.) slices (6, 9 and 12 mm) was carried out using aqueous solutions of sucrose of different concentrations (40, 50 and 60 % w/w) as osmotic media, at various fruit to solution ratios (1:2, 1:4 and 1:6). Total mass, water loss, solute gain and moisture content were determined for each sample at different time intervals (up to 6 h) of contact with the osmotic media. Regression analysis revealed that the osmotic dehydration kinetics depends strongly on sucrose concentration and slice thickness. The water loss and solute gain are more intensive at higher sucrose concentration and lower slice thickness. The effect of all the process parameters was observed to be significant at 10% level on both water loss and solute gain. Penetration and Magee model was fitted to the experimental data. Magee model was observed to represent water loss and solute gain more accurately as compared to Penetration model.